2011
DOI: 10.5761/atcs.cr.10.01595
|View full text |Cite
|
Sign up to set email alerts
|

Thoracoscopic Lobectomy for Treating Cancer in a Patient with an Unusual Vein Anomaly

Abstract: Various anatomical variants in pulmonary veins can have a serious effect on patients undergoing lung surgery. We present a case of a patient with an unusual pulmonary vein variation. Preoperative review of the patient's three-dimensional 64-row multidetector computed tomography imaging allowed us precise simulation and good orientation of the patient's vascular variant anatomy during surgery. Upper lobectomy through thoracoscopic approach was performed successfully in the case where the middle lobe vein might … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 8 publications
(8 reference statements)
0
8
0
Order By: Relevance
“…In particular, aberrant V 6 was not identified in previous reports. These minor anatomical variations in pulmonary veins can cause serious problems in patients undergoing lung surgery [7, 8]. For example, during right lower lobectomy in a patient with aberrant V 4+5 , if we cut an IPV with an aberrant V 4+5 , the right middle lobe would become dysfunctional after surgery.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, aberrant V 6 was not identified in previous reports. These minor anatomical variations in pulmonary veins can cause serious problems in patients undergoing lung surgery [7, 8]. For example, during right lower lobectomy in a patient with aberrant V 4+5 , if we cut an IPV with an aberrant V 4+5 , the right middle lobe would become dysfunctional after surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Preoperative identification of anomalous pulmonary vessels is thought to be important for avoiding injury to vessels and for further understanding of pulmonary anatomy. [1][2][3][4][5] Therefore, preoperative simulation of the surgical anatomy using imaging modalities is desirable. There are various advantages of this 3D-CT software that is based on volume-rendering techniques.…”
Section: Discussionmentioning
confidence: 99%
“…Suggested techniques to increase the safety of stapler passage include use of a red-rubber catheter (8)(9)(10)(11)(12)(13)(14) or a Penrose drain to guide the anvil, or use of silk sutures or vessel loops to maximize the space for anvil passage around the vessels. 29,57,58 Due to the low pressure pulmonary system, control of minor bleeding or oozing from staple lines, minor vasculature injuries, or parenchymal injuries often may be addressed adequately with a period of applied pressure.…”
Section: Surgical Techniquementioning
confidence: 99%
“…Less common venous drainage abnormalities reported include a common ostium for the left and right inferior pulmonary veins, 11,12 a lingular vein draining to the lower pulmonary vein, 13 a lateral segment vein of the middle lobe draining to the inferior pulmonary vein, and a superior segment vein draining directly into the left atrium. 4,14 Given the variability in the pulmonary venous drainage, some investigators have recommended routine formal preoperative venous system assessment with CT in all patients. 15 Some investigators have reported on the utility of preoperative CT for surgical planning 16 before thymectomy.…”
mentioning
confidence: 99%